Iowa Birdline update, March 24, 1991 - Scheib, Jameset al; Iowa Ornithologists' Unionet al (1991)
Notes for the Iowa Birdline update for March 24, 1991. Highlights include large numbers of waterfowl throughout the state although stormy weather has reduced viewing for much of the week. Epson - sheet feed/flatbed